Experiência expressiva : reflexões sobre a pintura de Willem de Kooning e Jorge Guinle Filho, contextos e linguagens - Leite, Luiz Carlos Fernandes Gonçalves (2013)
The Abstract Expressionism movement of great repercussion in the 50s, especially in the United States, initiated by the European avant-garde of the early twentieth century, as in informal sketches and paintings of Kandinsky, associated with emotional and